Sport talent identification and development in Nigeria: A preliminary investigation - Adegbesan, O.; Mokgwathi, M.; Omolawon, K.; Ammah, J.; Oladipo, I. (International Journal of Coaching Science, 2010)
Sport talent identification and development has become an interesting area of sport science research and the need to explore the basic fundamentals of this process necessitated the need for this preliminary investigation in Nigeria with the view to develop an ideal sport talent identification and development model that could be used for future recruitment and selection of young potencial athletes. Data was collected from 50 participants using a self-report instrument based on the talent identification and development characteristics and indicatiors. Results indicated that the physiological characteristic with the mean value (m = 15.26 ± sd = 8.44) was the most apparent considered variable used by the participants during the talent identification and development process when compared with other variables of motor skill, psychology, physiology and body morphology. Results on the indicators of sport talent identification and development revealed that majority of the participants, 27(54.0%) of coaches place emphases more on both the performance of basic motor skills and the combination of the anthropometrical, physical and physiological profiles of the young talented athletes during the talent identification and development process. Conclusively, this baseline information has given us insight to the future direction of this research which is the examination of these talent identification characteristics and basic indicators using descriptive, field and laboratory measures with an enlarged sample that will include sport scientists. This will enable us to analytically dissolve the potentials of the young athletes into a series of measurable and non-measurable components.